Predictive models for splenic response to JAK-inhibitor therapy in patients with myelofibrosis. Issue 4 (21st March 2019) - Menghrajani, Kamal; Boonstra, Philip S.; Mercer, Jessica A.; Perkins, Cecelia; Gowin, Krisstina L.; Weber, Alissa A.; Mesa, Ruben; Gotlib, Jason R.; Wang, Lixia; Singer, Jack W.; Talpaz, Moshe
Abstract: JAK inhibitors for myelofibrosis (MF) reduce spleen size, control constitutional symptoms, and may improve survival. We studied the clinical characteristics of 548 MF patients treated with JAK inhibitors from 2008 to 2016 to better understand predictors of splenic response. Response was defined as a 50% decrease in spleen size at early (3–4 months on therapy) and late (5–12 months) timepoints after therapy initiation. Early response positively correlated with higher doses of JAK inhibitor, baseline spleen size 5–10 cm, and hemoglobin. Early response negatively correlated with baseline spleen size >20 cm and high WBC. The strongest predictor of late response was whether a patient had a response at the earlier timepoint (OR 8.88). Our response models suggest that clinical factors can be used to predict which patients are more likely to respond to JAK inhibitors, and those who do not achieve an early response, i.e. within 3–4 months, should consider alternative treatments. Trial registration: ClinicalTrials.gov identifier: NCT01773187. Trial registration: ClinicalTrials.gov identifier: NCT02055781.